Effect of Low-temperature Storage on the Quality of Erythropalum scandens Blume of Different Varieties - Shangwen ZHANG; Tianwei YANG; Shiyu HUANG; Xiangjun ZHANG; Ting LI; Manrong GAO; Weihua YU; Ping MENG; Qian SHI (Shipin gongye ke-ji, 2023)
In order to explore the storage property of Erythropalum scandens Blume, this study compared and analyzed the changes of physiological and metabolic indexes of reducing sugar, soluble sugar, glucose, fructose, vitamin C, protein, crude fiber, water content and enzyme activity of Guichi 1 and Guichi 2 at 4 ℃. The results showed that the changes of water content of Guichi 1 and Guichi 2 were less than 3%, the content of various sugars and vitamin C showed downtrend, the change of protein content was not obvious, and the crude vitamin content showed an increasing trend during storage at 4 ℃. The main differences between the two varieties were reflected in the appearance, carbohydrates, vitamin C and various enzyme activities. At low temperature, the leaves of Guichi 2 shrank faster and faded significantly, carbohydrates and vitamin C decreased faster, and the activities of peroxidase, catalase and superoxide dismutase were lower than those of Guichi 1. Through comprehensive comparison, Guichi 1 was more resistant to storage than Guichi 2, and its nutrients, flavor, taste were also better than Guichi 2. The best shelf life of Guichi 1 was 10 days at 4 ℃ , and the best shelf life of Guichi 2 was 5 days at 4 ℃. This conclusion could provide a reference for the study of postharvest preservation of E. scandens.